2009
DOI: 10.1002/ajmg.a.32942
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors associated with paternal nondisjunction of chromosome 21

Abstract: Previous studies on relatively small samples of individuals with trisomy 21 caused by paternally derived errors have shown that: (1) advanced paternal age is not a risk factor for chromosome 21 nondisjunction (NDJ), (2) absence of recombination, but not the location of recombination is associated with paternal NDJ and (3) there is an excess of males among live-births with paternally derived trisomy 21. An excess of males is also observed among all individuals with trisomy 21. Using 128 families that had a chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
5
20
1
1
Order By: Relevance
“…In accordance with our results, other meiotic studies in fertile male donors reported G-group and sex chromosomes as the most susceptible to having no chiasmata at MI (Skakkebaek et al, 1973;Uroz et al, 2011) or no recombination foci at pachytene (Sun et al, 2006) (reviewed by Tempest, 2011). The absence of chiasmata has been correlated with an abnormal chromosome segregation in meiosis I both in trisomic 21 (Savage et al, 1998;Oliver et al, 2009) and 47,XXY conceptuses (Hassold et al, 1991;Lorda-Sanchez et al, 1992;Thomas et al, 2000). In the present work, chromosomes X, Y and 21 were the most commonly implicated in disomy in spermatocytes II, corroborating the results reported in spermatozoa from healthy men using FISH (reviewed by Templado et al, 2005Templado et al, , 2011.…”
Section: Low Chiasma Count In Human Spermatocytes Isupporting
confidence: 91%
“…In accordance with our results, other meiotic studies in fertile male donors reported G-group and sex chromosomes as the most susceptible to having no chiasmata at MI (Skakkebaek et al, 1973;Uroz et al, 2011) or no recombination foci at pachytene (Sun et al, 2006) (reviewed by Tempest, 2011). The absence of chiasmata has been correlated with an abnormal chromosome segregation in meiosis I both in trisomic 21 (Savage et al, 1998;Oliver et al, 2009) and 47,XXY conceptuses (Hassold et al, 1991;Lorda-Sanchez et al, 1992;Thomas et al, 2000). In the present work, chromosomes X, Y and 21 were the most commonly implicated in disomy in spermatocytes II, corroborating the results reported in spermatozoa from healthy men using FISH (reviewed by Templado et al, 2005Templado et al, , 2011.…”
Section: Low Chiasma Count In Human Spermatocytes Isupporting
confidence: 91%
“…Although we observed increased paternal meiosis-I errors in our sample, in contrast to previous reports of increased nondisjunction in paternal meiosis-II (Savage et al, 1998;Oliver et al, 2009), it is important to note that chromosome 21, which has one chaisma, is generally more prone to nondisjunction in normal males (Soares et al, 2001).…”
Section: Discussioncontrasting
confidence: 99%
“…The expected deviation in allele frequencies caused by aneuploidies in the SNP method differs based on the parental‐ and meiotic‐stage of origin of the aneuploidy (Figure ; Supplemental Figure S7), the rates of which vary substantially: 70% of nondisjunction events occur during maternal meiosis phase I (M1), leading to fetal inheritance of both maternal chromosomes, while 20% occur during meiosis phase II (M2), causing fetal inheritance of two copies of a single maternal chromosome . The remaining nondisjunctions are paternal in origin, with 3% originating from M1, and 7% from M2 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity of the SNP method at each fetal fraction was calculated by simulating 10,000 samples for each of the four types of meiotic nondisjunction and determining the proportion of trisomic samples for which the trisomy hypothesis had log‐odds ratio (LOR) below the threshold at which 99.87% of disomic samples would be called disomic (corresponding to the same specificity as the WGS test). The aggregate sensitivity of the SNP method was determined by calculating the weighted expectation of the sensitivity of detection of each fetal ploidy hypothesis multiplied by its prevalence …”
Section: Methodsmentioning
confidence: 99%